The Putative Role of Factor V Leiden and Prothrombin Mutations in Pregnancy Complications - Abdi, Fatemeh; Behboodi Moghadam, Zahra; Yazdkhasti, Mansoureh; Darooneh, Tayebeh; Rostami, Sahar (Archives of Advances in Biosciences, 2019)
Context: Thrombophilia is an inherited or acquired predisposition in developing thrombosis. The two common thrombophilia polymorphisms are factor V Leiden (FVL) and factor II/ prothrombin G20210A (PT) gene mutations which can contribute to negative pregnancy outcomes such as miscarriage, in-vitro fertilization (IVF) failure, preeclampsia, intrauterine growth restriction (IUGR), placental abruption, stillbirth, and pregnancy-associated venous thromboembolism. This review study sought to describe the effects of FVL and PT mutations on pregnancy complications. Evidence Acquisition: In this review study, a comprehensive search was performed on Iranian and international databases including MEDLINE, PubMed, Scopus, Web of Sciences, Proquest and Google Scholar for articles published during 1996-2018. Out of 220 reviewed articles, 80 papers were ultimately selected. Results: According to these 80 selected papers, the possible relations of PT and FVL with recurrent pregnancy loss (RPL) have been widely evaluated. Several studies indicated higher risk of recurrent early miscarriages, implantation failure and fetal loss after IVF among women with FVL and PT mutations. Conclusion: Observational studies have suggested the benefits of screening patients for thrombophilic polymorphisms in identification of women with higher risk of developing thromboembolic events and other related pregnancy complications. Based on such screening programs, prophylactic therapy can be limited to a selected group of women who truly need it.